Design and Implementation of an Arduino Uno Based Automatic Lighting Control System Using Passive Infrared (PIR) Sensors - Wafi Arifin; Sugeng Murdowo; Fata Nidaul Khasanah (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
In worship facilities such as mosques, electrical energy is frequently wasted due to lighting systems that remain active for extended periods, especially in restrooms and ablution (wudhu) areas. This condition is influenced by inconsistent usage patterns and limited user awareness in switching off lights after use. Despite these challenges, the application of Internet of Things (IoT) technology in such environments is still relatively minimal, mainly due to insufficient technological literacy and budget limitations. The Internet of Things (IoT) refers to a network of interconnected electronic devices capable of exchanging data and communicating through integrated systems. Motion detection is commonly employed to identify human presence, with the Passive Infrared Receiver (PIR) sensor being one of the most appropriate choices for this purpose. This sensor is widely recognized for its effectiveness in remote monitoring applications. This study aims to develop an IoT-based automatic lighting control system utilizing motion sensors to support energy efficiency and create an environmentally friendly environment. The research methodology includes requirement analysis, system implementation, and testing phases. The hardware realization, combined with programming using the Arduino IDE platform, successfully implements the automatic lighting control logic as designed. The system integrates PIR and ultrasonic sensors, and experimental results demonstrate that it is capable of accurately detecting objects within a defined range and responding rapidly and reliably to human movement.